Characterization of the archaeal community fouling a membrane bioreactor - Luo, Jinxue (2015)
Biofilm formation, one of the primary causes of biofouling, results in reduced membrane flux or increased transmembrane pressure and thus represents a major impediment to the wider implementation of membrane bioreactor (MBR) technologies for water purification. Most studies have focused on the role of bacteria in membrane fouling as they are the most dominant and best studied organisms present in the MBR. In contrast, there is limited information on the role of the archaeal community in biofilm formation in MBRs. This study investigated the composition of the archaeal community during the process of biofouling in an MBR. The archaeal community was observed to have lower richness and diversity in the biofilm than the sludge during the establishment of biofilms at low transmembrane pressure (TMP). Clustering of the communities based on the Bray–Curtis similarity matrix indicated that a subset of the sludge archaeal community formed the initial biofilms. The archaeal community in the biofilm was mainly composed of Thermoprotei, Thermoplasmata, Thermococci, Methanopyri, Methanomicrobia and Halobacteria. Among them, the Thermoprotei and Thermoplasmata were present at higher relative proportions in the biofilms than they were in the sludge. Additionally, the Thermoprotei, Thermoplasmata and Thermococci were the dominant organisms detected in the initial biofilms at low TMP, while as the TMP increased, the Methanopyri, Methanomicrobia, Aciduliprofundum and Halobacteria were present at higher abundances in the biofilms at high TMP.